M. T. Ramírez. The body by itself. From the phenomenology of the body to an ontology of the embodied self / trans. from Span. А. К. Zhaparova - А. К. Zhaparova (Омский научный вестник: Серия "Общество. История. Современность")
This article analyzes the «corporal turn» of Philosophy in XX Century. It parts from the revaluation of the body undertaken by Nietzsche against a tradition that probably emphasized too much the spirituality of the soul, ripping it from the body. A properly thought «Philosophy of the body» could bring back that reality which modern criticism has driven so far away. To offer a way out of universal solipsism, it is necessary a Philosophy of the body capable of rethinking Realism. MerlauPonty and Jean-Luc Nancy’s approaches to a Philosophy of corporality and of flesh are presented, then. The next section deals with the consequences of the corporal turn of Philosophy in relation to Ontology: it shows the way from the body to Being. The exemplar exteriority with which Nancy defines the body allows us to calibrate — in the sense of an immanent Philosophy which is not done, closed or definite — an atheism free from naïve and a kind of Ontological Realism free from abstractions or dogmatism. To close the cycle, «New Realism» approach, defended by Markus Gabril, Ferraris and Harman, amongst others, is presented and defended. The intention of this article is to present a way in which it is possible to formulate a new Ontology, a new conception of Being and existence, a realistic, materialistic ontology of the corporal being inasmuch the extra-corporal being.